Avaliação de usabilidade de usuários cegos e videntes no design responsivo e não-responsivo na web - Guntijo, M. R. (2016)
Provide accessibility is not easy but very important for a society where everyone can have equal conditions to exercise their rights as human beings, and when it comes to technology the need to have content access, especially on the Web, in an efficient manner, effective and satisfactory, raises concerns about usability and the evolution of design for Web, is observed in the literature the difficulties encountered by people with special needs, focus on the people with total visual impairment, where the task completion success rate in a environment is about 6 times worse than sighted people. The complexity of a Web page and the cognitive load are some of the factors that influence this performance. The new web trends explored the impact of a minimalist design, specifically Responsive Design, usability both blind as sighted people. We selected six websites, divided into 3 categories (Education, E-Commerce and Entertainment), responsive and another non-responsive in each category, participants performed tasks under scenarios built specifically for each category, we extract the time of completion, rate errors of tasks performed and also the comments made by participants to show whether Responsive Design has a positive or negative impact on usability. We conclude that the chance of a User complete the task in a responsive site is less than a non responsive, that age has an impact on the finalization of the tasks, that users with a college has a greater chance of completing tasks and that the blind average time is about 4.5 times greater for finalization tasks and on average 1.5 times more responsive when accessing sites.